⎣ ⎢ ⎢ ⎢ ⎢ ⎢ ⎢ ⎢ ⎢ ⎡ ⎝ ⎜ ⎜ ⎜ ⎜ ⎜ ⎜ ⎜ ⎜ ⎛ n = 1 ∑ 9 9 m = 1 ∑ n m 1 ⎠ ⎟ ⎟ ⎟ ⎟ ⎟ ⎟ ⎟ ⎟ ⎞ − 0 . 0 2 ⎦ ⎥ ⎥ ⎥ ⎥ ⎥ ⎥ ⎥ ⎥ ⎤ 2 1 = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Neat solution! :)
Thanks buddy! :)
Problem Loading...
Note Loading...
Set Loading...
⎣ ⎢ ⎢ ⎢ ⎢ ⎢ ⎢ ⎢ ⎢ ⎡ ⎝ ⎜ ⎜ ⎜ ⎜ ⎜ ⎜ ⎜ ⎜ ⎛ n = 1 ∑ 9 9 m = 1 ∑ n m 1 ⎠ ⎟ ⎟ ⎟ ⎟ ⎟ ⎟ ⎟ ⎟ ⎞ − 0 . 0 2 ⎦ ⎥ ⎥ ⎥ ⎥ ⎥ ⎥ ⎥ ⎥ ⎤ 2 1 = ? Then we can proceed as, ⎣ ⎢ ⎢ ⎡ ⎝ ⎜ ⎛ n = 1 ∑ 9 9 n ( n + 1 ) / 2 1 ⎠ ⎟ ⎞ − 0 . 0 2 ⎦ ⎥ ⎥ ⎤ 2 1 (as sum of first n natural numbers is n ( n + 1 ) / 2 )
Then, ⎣ ⎢ ⎢ ⎡ ⎝ ⎜ ⎛ n = 1 ∑ 9 9 n ( n + 1 ) 2 ⎠ ⎟ ⎞ − 0 . 0 2 ⎦ ⎥ ⎥ ⎤ 2 1 We can write the fraction as, ( n ) A + ( n + 1 ) B ( n ) ( n + 1 ) A ( n + 1 ) + B ( n ) So we can compare as follows, n ( n + 1 ) 2 = ( n ) ( n + 1 ) A ( n + 1 ) + B ( n ) 2 = A ( n + 1 ) + B ( n ) If n = 0 then, A = 2 If n = − 1 then, B = − 2 So we can write the fraction as, ⎣ ⎢ ⎢ ⎡ ⎝ ⎜ ⎛ n = 1 ∑ 9 9 ⎝ ⎛ ( n ) 2 − ( n + 1 ) 2 ⎠ ⎞ ⎠ ⎟ ⎞ − 0 . 0 2 ⎦ ⎥ ⎥ ⎤ 2 1
⎣ ⎢ ⎢ ⎡ ⎝ ⎜ ⎛ n = 1 ∑ 9 9 ( n ) 2 − n = 1 ∑ 9 9 ( n + 1 ) 2 ⎠ ⎟ ⎞ − 0 . 0 2 ⎦ ⎥ ⎥ ⎤ 2 1 Now, [ ( 1 2 + 2 2 + 3 2 + ⋯ + 9 9 2 ) − ( 2 2 + 3 2 + 4 2 + ⋯ + 1 0 0 2 ) − 0 . 0 2 ] 2 1 So all the terms from 2 2 to 9 9 2 will cancel out, The remaining part will be, [ ( 1 2 − 1 0 0 2 ) − 0 . 0 2 ] 2 1 ( 2 − 0 . 0 2 − 0 . 0 2 ) 2 1 ( 2 − 0 . 0 4 ) 2 1 ( 1 . 9 6 ) 2 1 1 . 4 So, the answer is 1 . 4 .